A new species of Ilex (Aquifoliaceae) from Jiangxi Province, China, based on morphological and molecular data - Jiang, Lei; Xu, Kewang; Fan, Qiang; Peng, Hua (Phytotaxa, 2017)
A new species, Ilex venusta, is described and illustrated from the Luoxiao Mountains, Jiangxi Province, China. It is included in a phylogenetic analysis using nuclear ribosomal nrITS and two plastid DNA markers (the atpB-rbcL and trnL-F spacers). This species is a member of Ilex sect. Paltoria., which can be distinguished from other sections in Ilex by their solitary pistillate inflorescences. The new species is similar to I. viridis and I. triflora, but it differs in its narrow leaves and slender trunk and branches.